2014
DOI: 10.1186/1465-9921-15-50
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound for the diagnosis of pneumonia in adults: a systematic review and meta-analysis

Abstract: BackgroundGuidelines do not currently recommend the use of lung ultrasound (LUS) as an alternative to chest X-ray (CXR) or chest computerized tomography (CT) scan for the diagnosis of pneumonia. We conducted a meta-analysis to summarize existing evidence of the diagnostic accuracy of LUS for pneumonia in adults.MethodsWe conducted a systematic search of published studies comparing the diagnostic accuracy of LUS against a referent CXR or chest CT scan and/or clinical criteria for pneumonia in adults aged ≥18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
284
5
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(317 citation statements)
references
References 35 publications
13
284
5
15
Order By: Relevance
“…The results of the trails conducted in Europe were similar to the data in China, suggesting the diagnosis accuracy is solid and might not be affected by race and region, only if the physicians were well-trained. Once again, our results confirmed LUS was a more powerful tool of rapid pneumonia detection than CXR.To date, three meta-analyses have summarized the data concerning LUS and pneumonia (4,11,34). In the analysis by Hu and colleagues (34), they studied the patients with pneumonia of all ages.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…The results of the trails conducted in Europe were similar to the data in China, suggesting the diagnosis accuracy is solid and might not be affected by race and region, only if the physicians were well-trained. Once again, our results confirmed LUS was a more powerful tool of rapid pneumonia detection than CXR.To date, three meta-analyses have summarized the data concerning LUS and pneumonia (4,11,34). In the analysis by Hu and colleagues (34), they studied the patients with pneumonia of all ages.…”
supporting
confidence: 76%
“…To date, three meta-analyses have summarized the data concerning LUS and pneumonia (4,11,34). In the analysis by Hu and colleagues (34), they studied the patients with pneumonia of all ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, increasing evidence supports superior diagnostic performance of lung ultrasound over chest radiography, such as when evaluating a pleural effusion (15), ruling out a pneumothorax in trauma (4), differentiating volume overload from an exacerbation of obstructive lung disease (16), or diagnosing pneumonia (17). The list of diseases that can be readily evaluated with lung ultrasound continues to expand, and now includes interstitial lung diseases (18), postoperative atelectasis (19), and diffuse alveolar hemorrhage (20).…”
Section: Commentarymentioning
confidence: 99%
“…In a recent systematic review comparing ultrasound with chest CT, lung ultrasound in adults was found to have a sensitivity of 94% and a specificity of 96% for pneumonia. 3 For patients arriving with undifferentiated shortness of breath and sepsis, PoCUS may be a valuable tool to help to rapidly diagnose the presence of important lung and pleural pathology.…”
Section: Introductionmentioning
confidence: 99%